Evolutionary relationships, hybridization and diversification under domestication of the locoto chile (Capsicum pubescens) and its wild relatives - Palombo, Nahuel E.; Weiss-Schneeweiss, Hanna; Carrizo García, Carolina (Frontiers in Plant Science, 2024)
Patterns of genetic variation in crops are the result of multiple processes that have occurred during their domestication and improvement, and are influenced by their wild progenitors that often remain understudied. The locoto chile, Capsicum pubescens, is a crop grown mainly in mid-highlands of South-Central America. This species is not known from the wild and exists only as a cultigen. The evolutionary affinities and exact origin of C. pubescens have still not been elucidated, with hypotheses suggesting its genetic relatedness and origin to two wild putative ancestral Capsicum species from the Central Andes, C. eximium and C. cardenasii. In the current study, RAD-sequencing was applied to obtain genome-wide data for 48 individuals of C. pubescens and its wild allies representing different geographical areas. Bayesian, Maximum Likelihood and coalescent-based analytical approaches were used to reconstruct population genetic patterns and phylogenetic relationships of the studied species. The results revealed that C. pubescens forms a well-defined monotypic lineage closely related to wild C. cardenasii and C. eximium, and also to C. eshbaughii. The primary lineages associated with the diversification under domestication of C. pubescens were also identified. Although direct ancestor-descendant relationship could not be inferred within this group of taxa, hybridization events were detected between C. pubescens and both C. cardenasii and C. eximium. Therefore, although hybrid origin of C. pubescens could not be inferred, gene flow involving its wild siblings was shown to be an important factor contributing to its contemporary genetic diversity. The data allowed for the inference of the center of origin of C. pubescens in central-western Bolivia highlands and for better understanding of the dynamics of its gene pool. The results of this study are essential for germplasm conservation and breeding purposes, and provide excellent basis for further research of the locoto chile and its wild relatives.